2018
DOI: 10.1057/s41304-017-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

The populism/anti-populism frontier and its mediation in crisis-ridden Greece: from discursive divide to emerging cleavage?

Abstract: Along with other South-European countries, since 2008, Greece has experienced deep economic and social dislocation, leading to a crisis of representation and triggering populist mobilisations and anti-populist reactions. This article focuses on the antagonistic language games developed around populist representations, something that has not attracted much attention in the relevant literature. Highlighting the need to study anti-populism together with populism, focusing on their mutual constitution from a discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 23 publications
1
34
0
4
Order By: Relevance
“…Despite the presence of the very same elements found in countries where populist actors have been receiving more support (for further detail on Greece, Spain, and Italy, see in this symposium Stavrakakis and Katsambekis 2018;Kioupkiolis and Seoane Pérez 2018;Bobba 2018, respectively), different kinds of constraints have, thus, made it particularly difficult for populist actors to thrive in Portugal. Portugal was one of the countries that most felt the Euro Crisis, and it has also experienced a crisis in the legitimacy of political elites and a climate of distrust against politicians in general, and, although less pronounced, the weakening of centrist political parties that has been happening in other countries (e.g.…”
Section: Portuguese Politics At the Fringes Of Populismmentioning
confidence: 99%
“…Despite the presence of the very same elements found in countries where populist actors have been receiving more support (for further detail on Greece, Spain, and Italy, see in this symposium Stavrakakis and Katsambekis 2018;Kioupkiolis and Seoane Pérez 2018;Bobba 2018, respectively), different kinds of constraints have, thus, made it particularly difficult for populist actors to thrive in Portugal. Portugal was one of the countries that most felt the Euro Crisis, and it has also experienced a crisis in the legitimacy of political elites and a climate of distrust against politicians in general, and, although less pronounced, the weakening of centrist political parties that has been happening in other countries (e.g.…”
Section: Portuguese Politics At the Fringes Of Populismmentioning
confidence: 99%
“…The Greek political system as a whole has long been characterized by the presence of populism (Pappas, 2013). Discourse analysis approaches have demonstrated that, during the lifespan of the Third Greek Republic, the populism/anti-populism divide was perpetually salient and become reactivated or even dominant under crisis conditions (Stavrakakis and Katsambekis, 2019).…”
Section: The Greek Crisis Version Of Populismmentioning
confidence: 99%
“…This has implications for long-lasting societal consequences (Kaplanoglou and Rapanos, 2018). As a result, Greece also went through significant political instability and is still mired in a crisis of political representation (Stavrakakis and Katsambekis, 2018). A by-product of this instability was an unexpected approval of the construction of new lignite-fired power plants, namely Ptolemaida V and Meliti II, of combined capacity of more than 1 GW (Simoglou et al, 2018), giving rise to doubts about how determined the Greek government is to actually deliver on its energy and climate commitments.…”
Section: Context: An Uncertain Environmentmentioning
confidence: 99%